Investigation for Collapsed Navigation Structures in The Mahakam River Delta by Bathymetry and Sonar - Efendi, Aco Wahyudi (JURNAL RIVET, 2025)
This study employed an integrated approach of side-scan sonar imaging and bathymetric surveying to precisely locate and characterize collapsed navigation structures within the dynamic Mahakam River Delta. This crucial waterway faces environmental challenges like strong currents and heavy siltation, threatening navigational aid integrity. Accurate identification of these submerged hazards is vital for safe shipping and future infrastructure development. Our findings demonstrated the effectiveness of combining these hydrographic methods to accurately map the seafloor and detect anomalies indicative of collapsed structures. Visual diving confirmed extremely poor underwater visibility, necessitating remote sensing. High-resolution bathymetric surveys successfully identified distinct riverbed anomalies, notably a collapsed structure at 00°50'13.29" S / 117°18'24.51" E, exhibiting a 1-1.5 meter elevation change at 4.5 meters depth. Acoustic data supported its man-made origin. These critical findings directly informed recommendations for repositioning affected navigation aids to a safer location at 00°50'16.29" S / 117°18'24.59" E, thus providing essential data for maritime safety and infrastructure management in complex riverine ecosystems.